Implementation of STEAM Method (Science, Technology, Engineering, Arts And Mathematics) for Early Childhood Developing in Kindergarten Mutiara Paradise Pekalongan - Ahmad Tabiin (Early Childhood Research Journal (ECRJ), 2019)
Suitable education in current development is surely required for every children in order to adapt with changes that occur, this certainly need to be addressed by looking for proper solution used in early childhood learning process, because early childhood education can give great benefit in growth and development for children, it also brings great positive impact for cognitive development, physical, emotional and social in children. Early childhood education is being talked about by applying new STEAM (Science, Technology, Engineering, Arts and Mathematics.) method. This method focuses on collaboration, communication, research, problem solving, and critical thinking ability. Through this approach, children are expected, not only academically intelligent but also socially, it also can stimulate children development optimally.     Research aims to find out the extent of implementation STEAM Method for early childhood developing. Method used in the research is qualitative descriptive with classroom teacher, Headmaster, and children in Mutiara Paradise Kindergarten as data source. Techniques of data collection are interview, observation and documentation. Technique of analysis and data collection are reduction, data display and conclusion drawing/verification. The result of the research shows the implementation of STEAM Method is very useful for children development, not only the children able to think critically in solving problem, but also children encounter very good social development.